Information management through human resources spectacles - Neil Duffy (South African Journal of Business Management, 1991)
The purpose with this article is to highlight the similarities of, and mutual dependence between, information management and human resource management. Information pervades almost everything we do. The information resource itself comprises applications, tools, people, organization, software, hardware and data. Many of the Issues that drive information systems today have strong human resources (HR) connotations: organizational learning, IS's role, contribution and alignment in the organization, end-user computing, IS implementation, change and organization design. Both IS and HR manage a key resource, require a strategic vision, are important components of the strategic plan, have similar components and are experiencing changing and increasingly important roles in their organizations. IS itself has become increasingly high touch over the years and as such needs to draw more and more on HR skills and support. In future the bottom line will depend on strength in both HR and IS and the ability of management to derive synergy from them.
Keywords: 650